From the street vendor to the entrepreneur: an ethnography in the street food trade in Recôncavo da Bahia (Research, Society and Development, 2021)
The article sought to understand the process of transition from street vendor to entrepreneur in street food, based on an ethnographic study carried out with workers in this trade, in the city of Santo Antônio de Jesus, Recôncavo da Bahia. Ethnography followed the analytical-interpretive line of Clifford Geertz. The field stage lasted seven months, using the techniques: systematic and participant observation and interviews with street vendors and key informants. Other alternative sources, such as reports from websites and local newspapers, made up the study. The analysis was based on theorists such as Ricardo Antunes, to discuss issues surrounding informal work, becoming an entrepreneur and the precariousness of street work. It was found that the implementation of the SAJ Legal Program, a political intervention aimed at reorganizing and restructuring street commerce in the city, culminated in the “recategorization” of street vendors to microentrepreneurs. Part of these did not recognize the “identity” of MEI, forged by the public power, meanings revealed in micro actions, such as resistance tactics and dissonant verbalizations, in the practice of labor. The Program revealed to adopt strategies based on neoliberal policies, when assuming the “entrepreneurial” discourse for regulation, to the detriment of a social protection policy for these subjects. Thus, the formalization of the street vendor to the MEI represented less of a resolutive policy than it had as a parameter of social hygiene and economic strategy. These manifestations showed that the corrosion of workers' rights, hidden under the veil of business discourse, primarily serve the financial market and represent the contingency of new forms of exclusion and precarious employment relationships.